Disease Modification in Asthma: Are We on the Right Way? A Multidisciplinary Expert Delphi Consensus (MODIASTHMA Consensus) - Miralles-López JC; Alvarez-Gutiérrez FJ; Delgado-Romero J; Quirce S; Soto-Campos JG; Andújar-Espinosa R; Cabrejos-Perotti S; Castilla-Martínez M; Flores-Martín I; Pajarón-Fernández MJ; Valverde-Molina J (Journal of Asthma and Allergy)
Juan Carlos Miralles-López,1,2 Francisco J Alvarez-Gutiérrez,3 Julio Delgado-Romero,4 Santiago Quirce,5,6 Jose Gregorio Soto-Campos,7 Ruben Andújar-Espinosa,2,8 Sheila Cabrejos-Perotti,2,9 Manuel Castilla-Martínez,2,10 Isabel Flores-Martín,2,11 Manuel José Pajarón-Fernández,2,12 José Valverde-Molina2,13,14 1Allergy Department, University General Hospital Reina Sofia, Murcia, Spain; 2Severe Asthma Association of the Region of Murcia. ASGRAMUR, Murcia, Spain; 3Medical and Surgical Unit of Respiratory Diseases, Hospital Universitario Virgen Del Rocío, Seville, Spain; 4Allergology Clinical Management Unit, Hospital Virgen Macarena, Seville, Spain; 5Department of Allergy, La Paz University Hospital, IdiPAZ, Madrid, Spain; 6CIBER of Respiratory Diseases (CIBERES), Madrid, Spain; 7Pneumology and Allergy Clinical Management Unit, University Hospital of Jerez, Jerez, Spain; 8Pulmonology Department. H. U. Virgen de la Arrixaca, Murcia, Spain; 9Allergy Department, University General Hospital Santa Lucia, Cartagena, Spain; 10Pulmonology Department, University General Hospital Los Arcos, San Javier, Spain; 11Allergy Department, Hospital Comarcal del Noroeste, Caravaca, Murcia, Spain; 12Allergy Department, Hospital de la Vega Lorenzo Guirao, Cieza, Spain; 13Paediatrics Department, University General Hospital Santa Lucia (Cartagena University Hospital Complex), Cartagena, Spain; 14IMIB Biomedical Research Institute, Murcia, SpainCorrespondence: Juan Carlos Miralles-López, Allergy Department, University General Hospital Reina Sofia, Murcia, Spain, Email juancmiralleslopez@gmail.comPurpose: With the advent of biological therapies, emerging concepts regarding establishing new targets in asthma management, such as disease modification, have entered the debate among the scientific community. The definitions that form the conceptual basis of this goal need to be agreed upon.Methods: A multidisciplinary expert group was assembled as the steering committee. A systematic literature review was conducted to identify the scientific background for constructing appropriate definitions. Based on the literature review and the clinical experience of the experts, the committee built a list of statements that could be applied to establish the definition of disease modification in asthma. After that, a Delphi validation was performed to assess the appropriateness of the list of statements. The questionnaire included a total of 22 statements, divided into “Essential criteria for disease modification in asthma” (5 statements) and “Disease modification indicators and other considerations” (17 statements). Panelists used a 9-point Likert scale to measure agreement on each statement. The cut-off point for high consensus was defined as a minimum score of 7 and had to be reached by at least two-thirds of the experts.Results: A total of 192 asthma experts voted on statements anonymously. Of those, 104 (54%) were Pneumologists, 65 (34%) were allergologists, and 23 (12%) were Pediatricians. An interim analysis of round 1 data was performed. All statements reached consensus on the first round, with a median score above 7 in all cases.Conclusion: In conclusion, in this Delphi study, a large number of experts in the management of severe asthma from different specialties agreed on the clinical-functional and pathophysiological aspects to be considered in order to try to achieve disease modification.Keywords: severe asthma, disease modification, delphi process, remission